Development of numeracy skills: Analysis of students in junior high schools in Ambon City based on teacher's perspective - R. H. Yanti Silitonga (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2023)
Numeration is important as it is a fundamental skill, but based on the evaluation of the Programme for International Student Assessment, showed that the student's numeration ability is still low. This study aims to analyze the various problems that occur in the development of numeration skills of high school students. The research was carried out at the Catholic High School in Ambon, with the subject of the research being teachers of mathematics and non-mathematics. This research is qualitative research using methods of narrative inquiry. Data collection techniques include questionnaires, interviews, and recording and documentation. The results of this research indicate that there are a number of issues with developing numeracy skills, one of which is the lack of implementation of classic game-based learning strategies. School facilities are inadequate to encourage increased student numeracy. The implementation of training for teachers to improve teacher numeracy is still rare, so it affects the lack of innovation of teachers in teaching by applying games as well as traditional games to improve numeracy.